Jade star - Coulter, Catherine (New York, N.Y. Signet, 2002)
Vowing to save a young girl from her painful past, Saint Morris marries her out of duty. He thinks of himself as her protector and brother. But she has other ideas....
82260
Keywords: Physicians' spouses -- Fiction; Children of clergy -- Fiction; Slave trade -- Fiction; Physicians -- Fiction; San Francisco (Calif.) -- Fiction; Love stories; Historical fiction